(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The goal of this article is to describe and interpret all economic and institutional facts which characterize the origin of the Sectorial System of Innovation (ssi) of avocados in Michoacán. The paper reconstructs the system of innovations as it is vital in order to shed light on the fact that the success of the development and evolution of this sector depended on imposing quality standards, as well as on the proactive corporate culture of certain producers.